Thermodynamic Analysis of Integrated Fuel Cell and Solar Energy Systems - Ratlamwala, Tahir Abdul Hussain (2011)
A Master of Science Thesis in Mechanical Engineering submitted by Tahir Abdul Hussain Ratlamwala entitled, "Thermodynamic Analysis of Integrated Fuel Cell and Solar Energy Systems," submitted in June 2011. Available are both soft and hard copies of the thesis.